Integrated Functional Analysis of the Nuclear Proteome of Classically and Alternatively Activated Macrophages - John E. Wiktorowicz; Imran H. Chowdhury; Susan Stafford; Subhadip Choudhuri; Nilay Dey; Nisha J. Garg (Hindawi Limited, 2019)
Macrophages (Mφ) play a central role in coordinating host response to pathogens, cellular injury, and environmental stimuli. Herein, we report multidimensional, nuclear proteomic analyses of protein expression and posttranslational modifications (PTMs) that control biological processes during Mφ activation. For this, Mφ were incubated with IFN-γ/LPS and IL-4, and their differentiation to proinflammatory (M1) and anti-inflammatory (M2a, referred as M2 for simplicity throughtout the manuscript) phenotypes was confirmed by detection of CD64 and CD206 surface markers and TNF-α, arginase I, and iNOS-dependent nitrite levels. We used a sequential method of organellar enrichment and labeling of nuclear fractions with BODIPY FL-maleimide fluorescence dye followed by two-dimensional electrophoresis (2DE) to capture quantitative changes in abundance and S-nitrosylated (SNO) proteome signatures. Exact same gels were then labeled with Pro-Q Diamond to detect protein phosphorylation. MALDI-TOF/TOF MS analysis of the protein spots with fold change of ≥1.5 in any of the groups yielded 229 identifications. We found that 145, 78, and 173 protein spots in M1 Mφ and 105, 81, and 164 protein spots in M2 Mφ were changed in abundance, S-nitrosylation, and phosphorylation, respectively, with respect to M0 controls (fold change: ≥1.5, p≤0.05). Targeted analysis by immunoprecipitation and Western blotting was performed to verify the differential abundance and phosphorylation levels of two of the proteins in M1 and M2 (vs. M0) Mφ. Ingenuity Pathway Analysis of the nuclear proteome datasets showed that the abundance and posttranslational (SNO and Phosphor) modifications of the proteins predicted to be involved in cytoskeletal organization/cell movement, phagocytosis/endocytosis, and cell proliferation/cell death were differentially regulated with proinflammatory and anti-inflammatory activation of Mφ.